(untitled) (Research, Society and Development, 2020)
The objective of the work was to evaluate the mechanical management of the soil and green manure cumulative during 22 months in the physical quality of the soil. The study was conducted at the UNICENTRO school farm in Guarapuava, PR. The design used was that of randomized blocks, in a 2x2x3 factorial scheme with 4 replications. Factor 1: scarification or not; Factor 2: sowing with double disc or furrowing rod; Factor 3: cover crops (turnip + black oats, crop mix and fallow). Soil physical attributes, penetration resistance (RP) and soybean yield were evaluated. The PR after 22 months of scarification showed a reduction in soil compaction, reflecting the performance of the partnership with green manures. Grooving rod was a viable alternative to reduce RP in the 0.05-0.15 m depth layer. The cultivation of turnip + oats or crop mix reduced PR during the commercial crop cycle. The physical attributes of the soil detected changes in the soil in the layer of 0-0.10 m of depth due to the performance of the cover plants, with greater macroporosity of the soil and lower density of the soil when scarifying the soil after 16 months of scarification and after the cultivation of green manure. The physical attributes of the soil did not detect changes in the 0-0.10 m and 0.10-0.20 m depth layer after soybean cultivation, 22 months after scarification. Scarification, green manure and the use of a furrow did not alter the productivity of the soybean crop.